On Henri Lefebvre, Queer Temporality and Rhythm: За Анри Лефевр, Queer врееменост и ритам - Ivanchikova, Alla (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Alla Ivanchikova | Ала Иванчикова Title (English): On Henri Lefebvre, Queer Temporality and Rhythm Title (Macedonian): За Анри Лефевр, Queer врееменост и ритам Translated by (English to Macedonian): no record Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 151-170 Page Count: 20 Citation (English): Alla Ivanchikova, “On Henri Lefebvre, Queer Temporality and Rhythm,” Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006): 151-170. Citation (Macedonian): Ала Иванчикова, „За Анри Лефевр, Queer врееменост и ритам“, Идентитети: списание за политика, род и култура, т. 5, бр. 1 (зима 2006): 151-170.